2017
DOI: 10.1093/mnras/stx468
|View full text |Cite
|
Sign up to set email alerts
|

Trace hydrogen in helium atmosphere white dwarfs as a possible signature of water accretion

Abstract: A handful of white dwarfs with helium-dominated atmospheres contain exceptionally large masses of hydrogen in their convection zones, with the metal-polluted white dwarf GD 16 being one of the earliest recognised examples. We report the discovery of a similar star: the white dwarf coincidentally named GD 17. We obtained mediumresolution spectroscopy of both GD 16 and GD 17 and calculated abundances and accretion rates of photospheric H, Mg, Ca, Ti, Fe and Ni. The metal abundance ratios indicate that the two st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 60 publications
2
79
0
Order By: Relevance
“…white dwarfs and their accretion of hydrogen have suggested that this is an extremely rare scenario (Gentile Fusillo et al 2017;Rolland et al 2018). As such our assumption that the relative number of helium-atmosphere white dwarfs should increase monotonically with cooling age is likely a robust one.…”
Section: Hydrogen Abundance In Dba White Dwarfsmentioning
confidence: 81%
See 1 more Smart Citation
“…white dwarfs and their accretion of hydrogen have suggested that this is an extremely rare scenario (Gentile Fusillo et al 2017;Rolland et al 2018). As such our assumption that the relative number of helium-atmosphere white dwarfs should increase monotonically with cooling age is likely a robust one.…”
Section: Hydrogen Abundance In Dba White Dwarfsmentioning
confidence: 81%
“…In principle the hydrogen abundances in DBA stars could be used to reconstruct their past evolution, but this is not accounting for the fact that accretion of planetary debris can significantly impact their hydrogen content. In fact, several DBA white dwarfs have orders of magnitude more hydrogen than would be possible by the convective dilution or convective mixing scenarios, and it is thought that the accretion of water-rich asteroids is the most likely explanation for the hydrogen abundance in these objects (Farihi et al 2011;Raddi et al 2015;Gentile Fusillo et al 2017). The study of spectral evolution is clearly complex and involves many competing models that need to be constrained with well defined samples of the local white dwarf population.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been detailed abundance measurements for only about 15 polluted WDs so far (see Jura & Young 2014;Jura et al 2015;Wilson et al 2015;Farihi et al 2016;Melis & Dufour 2017;Xu et al 2017;Gentile Fusillo et al 2017, and references therein), two of which show signs of planetary pollution in terms of composition and amount (see Section 1 for planetary pollution) (Jura et al 2009;Zuckerman et al 2011), and one with signs of volatile material pollution in the form of nitrogen (Xu et al 2017). While these are so far very small number statistics, these current results could imply that the planetary and volatile pollution rates are relatively high, on the order of ∼ 10 %, roughly consistent with our findings that ∼ 7.5% of all WDs could be polluted by Kuiper belt analog objects, while about 1% could be polluted by Neptune-like planets.…”
Section: Ekl Induced Wd Pollutionmentioning
confidence: 99%
“…In a volume-limited sample of DBs, the fraction of water is less than 1% of the total accreted mass ) even though there are some exceptions where the WDs have accreted a significant amount of water (e.g. Farihi et al 2013;Raddi et al 2015;Gentile Fusillo et al 2017). At least one WD has accreted a Kuiper-Belt-Object analog with 30% water and 10% carbon by mass (Xu et al 2017).…”
Section: Introductionmentioning
confidence: 99%